Integrated analysis of phase 1a and 1b randomized controlled trials; Treg-targeted cancer immunotherapy with the humanized anti-CCR4 antibody, KW-0761, for advanced solid tumors - Fujikawa, Kaoru; Saito, Takuro; Kurose, Koji; Kojima, Takashi; Funakoshi, Takeru; Sato, Eiichi; Kakimi, Kazuhiro; Iida, Shinsuke; Doki, Yuichiro; Oka, Mikio; Ueda, Ryuzo; Wada, Hisashi (PLOS ONE, 2023)
Introduction Regulatory T cells (Tregs) have attracted attention as a novel therapeutic target to augment the clinical efficacy of immunotherapy. We conducted phase Ia and Ib trials to examine the safety and efficacy of the anti-CCR4 antibody, KW-0761 (mogamulizumab), which may eliminate effector Tregs (eTregs). We herein overviewed the results of these trials, presented cases with a durable clinical response, and investigated factors associated with the clinical effects of KW-0761. Methods Forty-nine patients with CCR4-negative solid cancers were enrolled in the phase Ia and Ib trials on KW-0761. An integral analysis of safety, clinical responses, prognosis, blood laboratory data, and cancer testis antigen-specific immune responses was performed. Results Grade 3–4 treatment-related adverse events were reported in 21 (42.9%) out of 49 patients, all of which were manageable. A partial response and stable disease were observed in 1 and 9 patients, respectively. A durable clinical response was noted in 2 esophageal and 2 lung cancer patients. eTreg depletion in peripheral blood was confirmed in most patients, and eTreg depletion was sustained during the KW-0761 treatment. High lymphocyte levels at baseline and 2 weeks after the initiation of KW-0761 were associated with a favorable clinical outcome. Conclusions A durable clinical response was noted in some patients, and high lymphocyte levels before treatment initiation may be a biomarker for the efficacy of KW-0761. The synergistic effect of KW-0761 for depleting Tregs and other immunotherapies is expected in the future.